(3MGTjI Ydi GdTQGjYs - (3GdcQcj, GdYGedj, CHh GdMSf, GdeMbb GdKGfj, Ydj Hf GdMSjf Hf YHOGdYGdj, J (B940 (3g`s
(3ChdgG (B:s
(3eHJhQI GdGhd, hChd GdehLhO efGgG bhdg(B: ...(3aEf de jQM RhGdg bHd NQhL hbJ GdUdGI(B...(3gPG CMO GdCahGd GdKdGKI(B...s
(3BNQgG (B:s
(3eHJhQ GdBNQ, hBNQ GdehLhO efg bhdg(B: (3aEf Gdabjg EfeG jHMK YfgG ef MjK jUM hjaSO hef MjK jMd hjMQe (B...s
(3JHUQI GdYfhGf (B:s
(3MGTjI TQGFY GdESdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B4(3,U(B281s
(3eYLe GdeDdajf(B:(3L(B2(3,U(B430s
(3gOjI GdYGQajf(B:(3L(B1(3,U(B744s
Keywords: (3abg GdePGgH GdCNQis